2003
DOI: 10.1046/j.1524-4725.2003.29001.x
|View full text |Cite
|
Sign up to set email alerts
|

Indications for Lymph Node Dissection in the Treatment of Extramammary Paget's Disease

Abstract: In the treatment of extramammary Paget's disease, indications of lymph node dissection are an important issue as well as wide local excision. From this prospective study, we have developed an algorithm for indications of lymph node dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
4
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 14 publications
7
72
4
2
Order By: Relevance
“…We also found that among all of the patients with inguinal lymph node metastasis, the primary lesions involved the dermis. Other series demonstrated that the depth of involvement predicts a high possibility of inguinal lymph node metastasis [21,22]. This indicates that lymph node metastasis might originate from the primary lesion, rather than the recurrent lesion.…”
Section: Discussionmentioning
confidence: 96%
“…We also found that among all of the patients with inguinal lymph node metastasis, the primary lesions involved the dermis. Other series demonstrated that the depth of involvement predicts a high possibility of inguinal lymph node metastasis [21,22]. This indicates that lymph node metastasis might originate from the primary lesion, rather than the recurrent lesion.…”
Section: Discussionmentioning
confidence: 96%
“…Ensuring the depth as well as the extent of resection was an important feature of the operation. First, deep invasion of EMPD into subcutaneous tissues is possible [ 4,8 ] , and vertically inadequate resection could also lead to local recurrence. We controlled the surgical margin (horizontally and vertically), and the prevalence of local recurrence was much lower than that reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…A computed tomographic scan of the abdomen and pelvis is recommended to detect any associated or metastatic abdominal or genitourinary cancers [3]. If lymph node metastases are detected clinically or histopathologically, complete ilioinguinal lymph node dissection is indicated [8]. Screening with chest X-ray, colonoscopy, cystoscopy, and serum prostate-specific antigen levels is also performed by some physicians.…”
Section: Answermentioning
confidence: 99%